1994
DOI: 10.1128/mcb.14.8.5450
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of a variant human U6 small nuclear RNA gene is controlled by a novel, internal RNA polymerase III promoter.

Abstract: Promoter elements in the 5' flanking regions of vertebrate U6 RNA genes have been shown to be both necessary and sufficient for transcription by RNA polymerase III. We have recently isolated and characterized a variant human U6 gene (87U6) that can be transcribed by RNA polymerase III in vitro in the absence of any natural 5' or 3' flanking sequences. This gene contains 10 nucleotide differences from the previously characterized human U6 gene (wtU6) within the coding region but has no homology to wtU6 in the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 39 publications
(58 reference statements)
1
14
0
Order By: Relevance
“…At least four human U6 genes encoding identical RNAs are transcriptionally active to various degrees (Domitrovich and Kunkel 2003). Additionally, a variant of human U6 snRNA with nine substitutions and one nucleotide deletion is expressed under the control of an internal promoter, unlike other transcriptionally active human U6 genes (Tichelaar et al 1994(Tichelaar et al , 1998. The presence of multiple U6 genes of varying transcriptional activity has complicated their individual study, and whether paralogous but divergent U6 snRNAs exhibit differences in modification, localization or function is poorly understood.…”
Section: Number Of U6 Genesmentioning
confidence: 99%
“…At least four human U6 genes encoding identical RNAs are transcriptionally active to various degrees (Domitrovich and Kunkel 2003). Additionally, a variant of human U6 snRNA with nine substitutions and one nucleotide deletion is expressed under the control of an internal promoter, unlike other transcriptionally active human U6 genes (Tichelaar et al 1994(Tichelaar et al , 1998. The presence of multiple U6 genes of varying transcriptional activity has complicated their individual study, and whether paralogous but divergent U6 snRNAs exhibit differences in modification, localization or function is poorly understood.…”
Section: Number Of U6 Genesmentioning
confidence: 99%
“…However, the presence of these sequences along the human evolution has shaped the genome and new functional elements have been generated in most cases by a unique mechanism called retrotransposition [39]. Retrotransposition is the greatest remodeling force of the human genome, and it is currently represented by the Long Interspersed Nuclear Element 1 (LINE 1) [40][41][42][43]. These are 6-7kb elements that have all the machinery to be copied and mobilized into the genome.…”
Section: Mechanisms Of U6 Retrotranspositionmentioning
confidence: 99%
“…Assay. The minimal promoter constructs were made by annealing mutually priming, overlapping oligonucleotides spanning the entire length of the coding region and filling in the overhangs with T4 DNA polymerase as described previously (21). Analysis of the transcription of these constructs was carried out in HeLa S100 extract as described previously (20).…”
Section: Plasmid Constructs and In Vitro Transcriptionmentioning
confidence: 99%
“…We have previously described a naturally occurring sequence variant of the human U6 gene (20) and shown that it is controlled by a unique promoter (21). This RNA differs from the consensus mammalian U6 RNA at 10 of 107 residues, with none of the changes occurring at positions that are perfectly conserved throughout evolution (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation